MODEL PENGELOLAAN SAMPAH KOS-KOSAN DI KELURAHAN SEKARAN GUNUNGPATI SEMARANG - Sholeh, Muh.; Setyaningsih, Wahyu (Faculty of Social Science, Universitas Negeri Semarang, 2011)
The phenomenon of garbage is very interesting to study, especially in residential boarding for university students. Similarly, this happens in the village Sekaran where the majority of Unnes students stay. The research objective is to describe the organization, distribution process, waste management in boarding-lodging in the village Sekaran Gunungpati Semarang. To achieve these objectives, the research uses a qualitative approach that is supported by quantitative data to generate complete and objective research conclusions. The results of this study were a) The organizing of boarding-lodging waste is carried by scheduled in turn. The role of the inhabitants of boarding is to maintain the cleanliness of each room, cleaning the bathroom, collect trash from each room in the bin, burn, hoarding, and fees, b) the distribution of garbage in boarding-lodging starts from each room, then housed in each boarding. From the shelter there was garbage which was burned, dumped, and collected by offcers, c) the handling of waste is carried by burning, dumping, giving to scavengers, and being retrieved by the garbage offcer. There has been no attempt to process the waste into industri fertilizer. Keywords: Waste, management model